Green physical activity for leisure connects perceived residential greenspace and mental well-being - Li, Hansen; Li, Yun; Wang, Zhenhuan; Zhang, Guodong (Frontiers in Public Health, 2023)
Physical activity serves as a pivotal mediator in previous theoretical frameworks that link greenspace and human health. However, it remains unclear whether the domain of physical activity within and around greenspaces can alter the pathway. The present study recruited 668 participants online and examined a conceptual framework that explores the associations between residential greenspace and mental well-being, with a particular focus on the mediation effect of green physical activity (physical activity undertaken in and around greenspaces). Moreover, socio-demographic characteristics, including gender, age, household income, education status, marital status, and student status, were controlled for during the examination. The investigated green physical activities included leisure activities, transportation walking, and transportation cycling, and they were measured by a pre-established questionnaire. Meanwhile, mental well-being was measured by the WHO-5 well-being index, and residential greenspace was indicated by self-reported perceived greenspace and mean Normalized Difference Vegetation Index (NDVI) values within 500 meters (m) of residential radius. We found that both perceived greenspace (B = 1.852, p < 0.001) and NDVI 500 m (B = 3.230, p = 0.038) were positively associated with mental well-being. However, only perceived greenspace, not NDVI 500 m, exhibited positive associations with the three green physical activity items. Furthermore, only green physical activity for leisure (B = 0.223, p < 0.001), not for transportation (p > 0.05), mediated the relationship between perceived greenspace and mental well-being. Our findings reinforce previous studies on “greenspace-health” frameworks and underline the importance of leisure physical activity in promoting mental well-being.